2019
DOI: 10.1088/1748-9326/ab246e
|View full text |Cite
|
Sign up to set email alerts
|

Greenness trends and carbon stocks of mangroves across Mexico

Abstract: Mangroves cover less than 0.1% of Earth's surface, store large amounts of carbon per unit area, but are threatened by global environmental change. The capacity of mangroves productivity could be characterized by their canopy greenness, but this property has not been systematically tested across gradients of mangrove forests and national scales. Here, we analyzed time series of Normalized Difference Vegetation Index (NDVI), mean air temperature and total precipitation between 2001 and 2015 (14 years) to quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 82 publications
1
11
0
1
Order By: Relevance
“…(2018) also found that time‐series of 15‐years of four vegetation indexes (gNDVI, EVI, and NDVI) were significantly and negatively correlated with in situ data of temperature and salinity in the Yucatán Peninsula. However, the correlation NDVI‐ambient temperature is site‐specific and can be positive, especially in those sites found in temperate‐humid ecosystems where temperature is not the limiting factor for mangrove growth (Songsom et al., 2019; Vázquez‐Lule et al., 2019). Furthermore, the phenology inferred by Sentinel‐NDVI in our site agreed with field observations of mangrove phenology in the Gulf of California.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018) also found that time‐series of 15‐years of four vegetation indexes (gNDVI, EVI, and NDVI) were significantly and negatively correlated with in situ data of temperature and salinity in the Yucatán Peninsula. However, the correlation NDVI‐ambient temperature is site‐specific and can be positive, especially in those sites found in temperate‐humid ecosystems where temperature is not the limiting factor for mangrove growth (Songsom et al., 2019; Vázquez‐Lule et al., 2019). Furthermore, the phenology inferred by Sentinel‐NDVI in our site agreed with field observations of mangrove phenology in the Gulf of California.…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, they are mostly found in narrow strips along the coastline of the Gulf of California and adjacent to coastal deserts. Sonora and Baja California Sur, two Mexican states that border the Gulf of California, have a mangrove extension of 9,353 (1.42% of the national total) and 24,327 hectares (3.7% of the national total) respectively (Vázquez‐Lule et al., 2019). Although mangroves only occupy 1% of the arid ecosystems of northwestern Mexico, they can store about 28% of the total regional belowground carbon pool (Ezcurra et al., 2016; Ochoa‐Gómez et al., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Respectively, the tropical or subtropical broadleaf evergreen forests are the most productive ecosystems of Mexico (Murray‐Tortarolo et al, ). The wetland category, with high carbon sequestration potential, includes mangroves (and other coastal wetlands), which have been recognized as the ecosystems with higher carbon storage capacity from the site‐specific to the global scales (Adame et al, ; Atwood et al ; Vázquez‐Lule et al, ). Our results represent benchmarks for SOC monitoring across these land cover classes.…”
Section: Discussionmentioning
confidence: 99%
“…An initial investigation showed that~1/3 of the apparent GPP increase from 2000 to 2019 was due to interpolation. We are currently investigating this topic further, as other work has found increasing GPP over time for mangroves in Mexico (Vázquez-Lule et al, 2019). One potential future avenue is to use data from NOAA's Coastal Change Analysis Program to map dynamic changes , although this approach could coarsen the spatial resolution and bring greater wetland classification errors.…”
Section: Reducing Bc Model Uncertaintymentioning
confidence: 98%